Efektivitas Program Penyusunan Peta Peluang Investasi dalam Mendukung Pencapaian Realisasi Investasi di Indonesia (Studi di Kementerian Investasi/Badan Koordinasi Penanaman Modal Republik Indonesia) - Muhammad Khoirul Anwar; Sri Yunanto; Dini Gandini Purbaningrum; Reza Rizkynata (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
Indonesia's economic growth in 20221 shows a positive figure, namely 3.69% yoi. This growth experienced a significant increase compared to economic growth in 2020 which experienced a contraction at minus 2.07%. This economic growth certainly gives good hope for the growth and movement of the Indonesian economy in 2022. One of the strategies implemented by the Ministry of Investment/BKPM RI is the preparation of an Investment Opportunity Map that is ready to be offered to Investors. This program is State facilitation for investors to invest their capital by providing all the necessary information in the form of a pre-financial study (pre-FS). The research aims to describe the effectiveness of the program for compiling investment opportunity maps in supporting the achievement of investment realization in Indonesia at the Ministry of Investment/BKPM RI. The method used is descriptive with a qualitative approach, the output of which is the publication of the ISSN national journal OJS and national seminars. The results of this study indicate that the PPI program is effective in increasing investment realization in Indonesia. The seven indicators consisting of Clarity of Goals to be Achieved, Clarity of Strategy for Achievement of Goals, Steady Policy Analysis and Formulation Process, Mature Planning, Proper Programming, Availability of Facilities and Infrastructure, Educational Monitoring and Control System all show a high level of effectiveness.